Circulating MicroRNAs in Patients with Vulvar Squamous Cell Carcinoma and Its Precursors - Julia Rymuza; Angelika Długosz; Kamil Zalewski; Artur Kowalik; Mateusz Bujko; Magdalena Kowalewska (Non-Coding RNA)
Objectives: Vulvar squamous cell carcinoma (VSCC) is a rare gynecologic malignancy, with most cases arising from differentiated vulvar intraepithelial neoplasia (dVIN). Approximately one-third of VSCC cases originate from high-grade squamous intraepithelial lesions (HSILs), which are associated with persistent infection by varieties of high-risk human papillomavirus (hrHPV). This study aimed to quantify the circulating microRNAs (miRNAs) in the plasma of patients with premalignant conditions (dVIN and HSILs) and VSCC using TaqMan Low-Density Arrays. Methods: Plasma samples were collected from 40 patients, including those treated for HSILs, dVIN, and VSCC. Quantitative real-time PCR (qRT-PCR) identified the circulating miRNAs differentially expressed in the plasma of VSCC patients compared to patients with precancerous lesions. Results: A total of 31 differentially expressed miRNAs (DEMs) were found to be significantly upregulated in plasma from VSCC patients compared to precancerous cases. None of the analyzed miRNAs were able to distinguish VSCC cases based on hrHPV tumor status. Conclusions: This study provides strong evidence that a distinct set of miRNAs can differentiate between plasma samples from VSCC patients and those with precancerous lesions. Thus, these DEMs have potential diagnostic and prognostic value. “Predisposing” DEMs could be developed as biomarkers to aid in the assessment of vulvar lesions, helping to exclude or confirm progression toward cancer.